Hierarchical architecture of polyaniline nanoneedle arrays on electrochemically exfoliated graphene for supercapacitors and sodium batteries cathode - Yingjuan Sun; Liansheng Jiao; Dongxue Han; Faxing Wang; Panpan Zhang; Hongyan Li; Li Niu (Materials & Design, 2020)
This study reports an efficient and straightforward method to construct hierarchical architectures for electrochemical energy storage. The composites, which are based on needle-like polyaniline (PANI) and high quality electrochemical exfoliation graphene (EG), can be a potential candidate for sodium batteries cathode due to favorable structural and morphological properties. Kinetics analysis of cyclic voltammetry has evidenced the diffusion controlled and pseudocapacitive controlled contributions of charge storage in the EG-PANI composite cathode. For the first time, the full sodium cell based on the EG-PANI composite was constructed and the rate capacities reached up to 64 mA h g−1 at the current densities of 100 mA g−1. In addition, the readily available composites bearing high conductivity and high-quality contact interface also enable the design of efficient supercapacitor. Specifically, the specific capacitance of EG-PANI composites electrode is 736 F g−1 at 0.2 A g−1, and the specific capacitance can be achieved to 410 F g−1 under 10 A g−1 (high current density). The synergistic effect of EG and PANI provides a remarkable storage capacity. Our work has inspired the search for large scale and hierarchical architectures materials for electrochemical energy storage. Keywords: Electrochemical exfoliation of graphene, Needle-like polyaniline, Cathode, Sodium batteries, Supercapacitor